Epistimologi Sarung sebagai Identitas dan Simbol Pendidikan Karakter di Pondok Pesantren Mambaul Ulum Bata-Bata Pamekasan - Syakir, Ahmad Fauzan; Qomaruzzaman, Ahmad; Ahsani, Abdurrohman Nur (Lembaga Pendidikan Ma'arif Nahdlatul Ulama, Kabupaten Malang, Indonesia, 2023)
The santri each have their own distinct identity thanks to the sarong. In addition, at the Mambaul Ulum Bata-Bata Pamekasan Islamic boarding school, the sarong is one of the media, a means of preserving and developing character education that always preserves Islamic culture and religious souls.With a material culture perspective as a concept of local culture and national heritage,